RANCANG BANGUN APLIKASI KEARSIPAN IJAZAH BERBASIS WEBSITE DALAM UPAYA MENINGKATKAN EFISIENSI LAYANAN ADMINISTRASI PENDIDIKAN - Luki Lukmanul Hakim; Sarmidi Sarmidi; Rikha Surtika Dewi (JOURNAL SAINS STUDENT RESEARCH, 2025)
Diploma archive management in many schools is still done manually, often leading to challenges such as lengthy search processes, the risk of document damage, and delays in administrative services. This study aims to design and implement a web-based diploma archiving application to improve the efficiency, security, and accuracy of educational administration services. The study employed a descriptive qualitative approach with a case study method at SMK Asy Syifa 02 Parigi. The Waterfall software development model encompasses the stages of needs analysis, system design, implementation, testing, and maintenance. The system was built using PHP and MySQL, with key features including integrated recording, searching, grouping, and reporting of diploma archives. Functional testing using the Black Box method demonstrated that all features functioned as designed. Feasibility assessments from users and software experts confirmed the system's feasibility. Implementation of this application is expected to minimize the risk of document loss or damage, accelerate the search process, and support digital transformation in educational administration.